Polymer solid electrolyte of fluoride-free interface layer, in-situ polymerization preparation method and application

Through the in-situ polymerization preparation method of polymer solid electrolyte with a fluorine-free interface layer, the problems of large solid-solid interface impedance and low circulation stability of solid-state lithium metal batteries are solved, high lithium ion conductivity and good interface contact are achieved, and the cycling performance of the battery is significantly improved.

CN119735735APending Publication Date: 2025-04-01SHENZHEN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411691855.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Solid-state lithium metal batteries cause microcracks due to large solid-solid interface impedance and battery cyclic expansion and contraction, resulting in low battery capacity cycling stability.

Method used

The in-situ polymerization preparation method of polymer solid electrolyte with a fluorine-free interface layer is adopted. By mixing vinyl monomers and organic solvents, adding metal lithium salts and initiators to form a precursor solution, and radical in-situ polymerization is carried out at a certain temperature to form a polymer network structure.

Benefits of technology

It improves lithium ion conductivity, inhibits the growth of lithium dendrites, maintains good battery electrode interface contact, and significantly improves the battery's Coulomb efficiency and charge and discharge cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735735A_ABST
    Figure CN119735735A_ABST
Patent Text Reader

Abstract

The invention provides a polymer solid electrolyte of a fluoride-free interface layer, an in-situ polymerization preparation method and application, a monomer and an organic solvent are mixed, a lithium salt and an initiator are added to form a precursor solution, and the monomer is subjected to free radical in-situ polymerization at a certain temperature to form a polymer with a macromolecular network structure. Wherein at least one of the monomers is an oxygen-containing monomer. Compared with the prior art, the polymer solid electrolyte with the fluoride-free interface layer has high lithium ion conductivity and can effectively inhibit the growth of lithium dendrites. In addition, good interface contact is kept between the in-situ polymerization fluorine-free polymer solid electrolyte and a battery electrode, so that the in-situ polymerization fluorine-free polymer solid electrolyte has excellent coulombic efficiency and charge-discharge cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and in particular relates to a polymer solid electrolyte without a fluorine interface layer, an in-situ polymerization preparation method and an application thereof. Background Art

[0002] Lithium-ion batteries are widely used in various fields such as electronics, automobiles, aviation, and deep sea. The high energy density and high safety of lithium-ion batteries have become the goals pursued by the current society. Traditional liquid lithium-ion batteries are mainly electrolytes composed of some organic solvents and lithium salts. The most widely used organic solvents are carbonates and organic ethers. Commonly used carbonate organic solvents include: dimethyl carbonate, ethylene carbonate, diethyl carbonate, propylene carbonate, methyl ethyl carbonate, etc. Organic ether solvents include: ethylene glycol dimethyl ether, ethylene glycol diethyl ether, dioxolane, dioxane, trioxane, tetrahydrofuran, etc. However, this type of organic solvent is flammable and has great safety hazards. When a short circuit occurs inside the battery, the local temperature is too high and a fire is caused, causing serious personal safety.

[0003] In order to solve the safety risks of traditional batteries and improve the energy density of batteries at the same time, researchers use lithium metal anodes to replace traditional graphite anodes. High energy density lithium metal batteries have the highest theoretical capacity (3860mAhg -1 ) and the lowest electrochemical potential (-3.04V) are expected to be used as the next generation battery system. At the same time, the use of solid electrolytes to replace traditional liquid organic electrolytes can fundamentally solve the safety problems of liquid batteries. The use of solid electrolytes has become a new trend to improve battery energy density and safety, avoiding the risk of electrolyte leakage from the source. Therefore, the development of next-generation solid-state batteries has become a competitive field for researchers and major new energy companies around the world.

[0004] In recent years, researchers have been working hard to develop lithium-ion battery systems. In solid-state battery systems, the interface contact between the solid electrolyte and the electrode is poor, the impedance between the solid-solid interface inside the battery increases, and the battery produces a large number of internal microcracks due to the continuous expansion and contraction of the positive and negative electrodes in the later stages of the cycle, which ultimately leads to rapid failure of the solid-state lithium metal battery. This is the main factor leading to the low capacity cycle stability of the battery. However, solid polymer electrolytes have more advantages due to their high flexibility and processability, excellent mechanical properties, low density and high electrode / solid electrolyte interface contact area. However, due to the low ionic conductivity of solid polymer electrolytes at room temperature (<10 -4 S cm -2), narrow electrochemical window, poor electrochemical stability, and the preparation of high energy density solid polymer batteries with solid polymer electrolyte interface stability is still a great challenge. Therefore, improving the interface contact between polymer electrolyte and electrode to obtain a higher energy density solid-state battery has become the top priority of current lithium-ion battery research. Summary of the invention

[0005] The first object of the present invention is to provide an in-situ polymerization method for preparing a polymer solid electrolyte having a fluorine-free interface layer.

[0006] To this end, the above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0007] An in-situ polymerization preparation method for a polymer solid electrolyte without a fluorine interface layer comprises the following steps:

[0008] S1, preparing a liquid electrolyte by mixing a vinyl monomer and an organic solvent in a certain ratio;

[0009] S2, adding a certain amount of metal lithium salt to the liquid electrolyte prepared in step S1, and adding an initiator to obtain a quasi-solid electrolyte precursor liquid;

[0010] S3, heating the quasi-solid electrolyte precursor obtained in step S2 or subjecting it to ultraviolet light for static molding to obtain a cross-linked polymer solid electrolyte;

[0011] The heating temperature is 15℃~90℃, the heating time is 0.5h~36h, and the standing time is 0.5h~72h;

[0012] The vinyl monomer is a fluorine-free monomer.

[0013] While adopting the above technical solutions, the present invention may also adopt or combine the following technical solutions:

[0014] As a preferred technical solution of the present invention: the vinyl monomer is: vinyl carbonate (VC), vinyl ethylene carbonate (VEC), N,N'-methylenebisacrylamide (MBA), polyethylene glycol methacrylate (PEGDA), polyethylene glycol dimethacrylate (PEGDMA), polyethylene glycol methyl ether methacrylate (PEGMEA), acrylonitrile (AN), hydroxyethyl acrylate (HEA), maleic anhydride (MA), pentaerythritol tetraacrylate (PETEA), pentaerythritol triacrylate (PETA), 3-(isobutyleneoxy)propyltrimethoxysilane (MPS), tri(ethylene glycol) divinyl ether (TEG), methyl methacrylate (MMA), methyl acrylate (MA), acrylic acid (AA), glycidyl methacrylate (GMA), acrylic acid-cage polysilsesquioxane (POSS) or a combination of the two or more thereof.

[0015] As a preferred technical solution of the present invention: the organic solvent is: ethylene glycol dimethyl ether (DME), 1,2-dimethoxypropane (DMP), propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl formate (MF), methyl acetate (MA), N,N'-dimethylacetamide (DMA), fluoroethylene carbonate (FEC), methyl propionate (MP), ethyl propionate (EP), ethyl acetate (EA), γ-butyrolactone (GBL), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2MeTIF), 4-methyl-1,3-dioxolane (4MeDOL), dimethoxymethane (DMM), triethylene glycol dimethyl ether (DG), dimethyl sulfone (MSW), ethylene sulfite (ES), propylene sulfite (PS), dimethyl sulfite (DMS), diethyl sulfite (DES), 1,3-dioxolane (DOL), tetrahydrofuran (THF), vinylene carbonate (VC), fluoroethylene carbonate (FEC), and trioxymethylene (TOM) One or more combinations thereof.

[0016] As a preferred technical solution of the present invention: the metal lithium salt is: lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonate)imide [LiN(CF3SO2)2, LiTFSI] and its derivatives, perfluoroalkyl lithium phosphate [LiPF3(C2F5)3, LiFAP], lithium tetrafluorooxalate phosphate [LiPF4(C2O4)], lithium bis(oxalate oxalate borate) (LiDFOB), lithium bis(oxalate borate) (LiBOB), lithium tri(catechol) phosphate (LTBP), sulfonated polysulfonamide lithium salt, lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium nitrate (LiNO3), lithium carbonate (LiCO3), lithium chloride (LiCl) one or more combinations thereof.

[0017] As a preferred technical solution of the present invention, the initiator is: azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), azobisisovaleronitrile (AMBN), azoisobutylcyanoformamide (CABN), azobiscyclohexylcarbonitrile (ACCN), dimethyl azobisisobutyrate (AIBME), azobisisobutylamidine hydrochloride (AIBA), benzoyl peroxide, lauroyl peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, diisobutylene hydroperoxide Propylbenzene, tert-butyl perbenzoate, tert-butyl pervalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, potassium persulfate, sodium persulfate, ammonium persulfate, 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone or a combination of more thereof.

[0018] As a preferred technical solution of the present invention: the mass percentage of the initiator to the monomer is 0.01%-10%.

[0019] The second object of the present invention is to provide a polymer solid electrolyte without a fluorine interface layer.

[0020] To this end, the above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0021] A polymer solid electrolyte with a fluorine-free interface layer is prepared by the in-situ polymerization preparation method of the polymer solid electrolyte with a fluorine-free interface layer as described above.

[0022] Another object of the present invention is to provide the use of the polymer solid electrolyte without fluorine interface layer as described above in the preparation of lithium metal batteries.

[0023] The present invention provides a polymer solid electrolyte with a fluorine-free interface layer, an in-situ polymerization preparation method and application, wherein a monomer and an organic solvent are mixed, a lithium salt and an initiator are added to form a precursor solution, and the monomer is subjected to free radical in-situ polymerization at a certain temperature to form a polymer with a high molecular network structure, wherein the monomer is a fluorine-free monomer. Compared with the prior art, the polymer solid electrolyte with a fluorine-free interface layer provided by the present invention has high lithium ion conductivity and can effectively inhibit the growth of lithium dendrites. In addition, the in-situ polymerized fluorine-free polymer solid electrolyte maintains good interface contact with the battery electrode, so that it has excellent coulomb efficiency and charge-discharge cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the infrared spectrum of the polymer solid electrolyte prepared in Example 1.

[0025] Figure 2 This is a graph showing the test results of the lithium ion migration number of the polymer solid electrolyte prepared in Example 1.

[0026] Figure 3 This is a test result diagram of the lithium ion migration number of the liquid electrolyte prepared in Comparative Example 1.

[0027] Figure 4 This is the X-ray photoelectron spectrum of the polymer solid electrolyte interface layer prepared in Example 1.

[0028] Figure 5 This is the X-ray photoelectron spectrum of the liquid electrolyte interface layer prepared in Comparative Example 1.

[0029] Figure 6 It is a comparison diagram of constant current charge and discharge curves of the symmetrical battery of Example 1 and Comparative Example 1.

[0030] Figure 7 It is a comparison chart of the charge and discharge cycle performance test of the batteries in Example 1 and Comparative Example 1 at 1C rate. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0032] In addition, the meaning of "and / or" appearing in the full text includes three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or a solution that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] In order to enable the details and operations of the above-mentioned embodiments of the present invention to be clearly understood by those skilled in the art, as well as to demonstrate the significant improvement in the performance of the cross-linked polymer quasi-solid electrolyte with a fluorine-free interface layer and its preparation method and application in the embodiments of the present invention, the above-mentioned technical scheme is illustrated by means of multiple embodiments below.

[0034] 1. Preparation of polymer solid electrolyte

[0035] Example 1

[0036] Propylene carbonate (PC) and ethylene glycol dimethyl ether (DME) are mixed in a volume ratio of 1:3, and 0.2M lithium nitrate (LiNO3) (after being configured into an electrolyte salt solution, the molar concentration of lithium nitrate is 0.2M) and 1M lithium bis(oxalatoborate) (LiBOB) (after being configured into an electrolyte salt solution, the molar concentration of lithium bis(oxalatoborate) is 1M) are added to the solvent to mix and obtain an electrolyte salt solution;

[0037] Adding 40% of the mass fraction of the above-mentioned electrolyte salt solution of vinylene carbonate (VC) monomer and mixing with the above-mentioned prepared electrolyte solution, then adding N,N'-methylenebisacrylamide (MBA), the molar number of MBA accounts for 5% of the molar number of vinylene carbonate, and adding 0.5% of the initiator azobisisobutyronitrile (AIBN) monomer mass fraction (the mass of the initiator accounts for the mass of the total monomers) to obtain a solid electrolyte precursor liquid;

[0038] The obtained solid electrolyte precursor liquid was cured at 70° C. for 6 hours to obtain a cross-linked polymer solid electrolyte (PVM).

[0039] Comparative Example 1

[0040] Propylene carbonate (PC) and ethylene glycol dimethyl ether (DME) are mixed in a volume ratio of 1:3 to obtain a mixed solvent;

[0041] 0.2 M lithium nitrate (LiNO3) and 1 M lithium bis(oxalatoborate) (LiBOB) are added to the mixed solvent to obtain a liquid electrolyte.

[0042] 2. Preparation of batteries containing polymer solid electrolytes

[0043] Take the polymer solid electrolyte prepared in Example 1 as an example to prepare a battery:

[0044] Positive electrode preparation: Add lithium nickel cobalt manganese oxide (NCM811), conductive carbon black, and polyvinylidene fluoride to an appropriate amount of N-methylpyrrolidone (NMP) in a ratio of 8:1:1, mix and stir at room temperature for 24 hours, then coat on a 200-micron thick aluminum foil, and vacuum dry at 80°C for 24 hours. Cut the electrode into 12 mm diameter discs, and the loading of active material NCM811 is 3 mg / cm 2 .

[0045] Negative electrode material: Commercially available 14mm diameter, 0.5mm lithium metal disc.

[0046] Battery assembly: The polymer solid electrolyte prepared in Example 1 is assembled into a battery in the order of negative electrode shell, spring sheet, gasket, lithium metal, separator, precursor liquid, NCM811 positive electrode sheet, and positive electrode shell. After assembly, the battery is pressed and sealed, and heated at 70°C and allowed to stand for 6 hours to ensure in-situ solidification of the precursor liquid.

[0047] Results and Discussion:

[0048] like Figure 1 As shown, 1630cm in the infrared spectrum -1 The infrared characteristic peak at the carbon-carbon double bond disappears and is replaced by the peak at 1750cm -1 and 1667cm -1 There are obvious C=O and HN-C=O infrared characteristic peaks, indicating that the monomer can be successfully polymerized into electrolyte polymer.

[0049] like Figure 2-3 As shown, the lithium ion transfer number of the polymer solid electrolyte prepared in Example 1 is 0.77, and the lithium ion transfer number of the liquid electrolyte prepared in Comparative Example 1 is 0.44. The hydrogen bond interaction between the MBA cross-linking sites and the anions and the weak binding ability of the polymerized chain segments VC to lithium ions promote the transmission of lithium ions in the polymer network.

[0050] like Figure 4-5As shown in the figure, compared with Comparative Example 1, the content of Li2O formed in Example 1 is higher. This shows that the cross-linked polymer electrolyte formed by the in-situ polymerization method of the present invention successfully constructs a fluorine-free interface layer mainly composed of Li2O. When the content of Li2O in Example 1 is high, the cycle of its symmetrical battery in constant current charge and discharge is more stable, as shown in FIG. Figure 6 At the same time, the comparison of the charge-discharge cycle performance test of the battery prepared by the polymer solid electrolyte prepared in Example 1 and the battery prepared by the liquid electrolyte prepared in Comparative Example 1 at 1C rate is shown in the figure below. Figure 7 As shown, after 800 cycles of charge and discharge, the discharge capacity and retention rate of the battery prepared by the polymer solid electrolyte prepared in Example 1 are: 121mAh / g, 84.7%. The specific capacity of the liquid electrolyte prepared in Comparative Example 1 has decayed to 10.6mAh / g after 50 cycles, indicating that the fluorine-free interface layer mainly composed of Li2O can promote the uniform deposition of lithium ions, inhibit the growth of dendrites, and achieve stable charge and discharge cycles of lithium metal batteries, so that the battery with the polymer solid electrolyte prepared in Example 1 has excellent charge and discharge cycle performance.

[0051] The above-mentioned specific implementation methods are used to explain the present invention and are only preferred embodiments of the present invention, rather than limiting the present invention. Any modifications, equivalent substitutions, improvements, etc. made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a polymer solid electrolyte having a fluorine-free interface layer by in-situ polymerization, characterized in that: The method comprises the following steps: S1. Preparing a metal lithium salt and an organic solvent into an electrolyte solution, then adding a vinyl monomer into the electrolyte solution, and adding an initiator to obtain a quasi-solid electrolyte precursor solution; S2, heating the obtained quasi-solid electrolyte precursor liquid or placing it under ultraviolet light to form it, and obtaining a cross-linked polymer solid electrolyte; The heating temperature is 15℃~90℃, the heating time is 0.5h~36h, and the standing time is 0.5h~72h; The vinyl monomer is a fluorine-free monomer.

2. The in-situ polymerization preparation method of a polymer solid electrolyte having a fluorine-free interface layer according to claim 1, characterized in that: The vinyl monomer is: vinyl carbonate (VC), vinyl ethylene carbonate (VEC), N,N'-methylenebisacrylamide (MBA), polyethylene glycol methacrylate (PEGDA), polyethylene glycol dimethacrylate (PEGDMA), polyethylene glycol methyl ether methacrylate (PEGMEA), acrylonitrile (AN), hydroxyethyl acrylate (HEA), maleic anhydride (MA), pentaerythritol tetraacrylate (PETEA), pentaerythritol triacrylate (PETA), 3-(isobutylene acyloxy)propyltrimethoxysilane (MPS), tri(ethylene glycol) divinyl ether (TEG), methyl methacrylate (MMA), methyl acrylate (MA), acrylic acid (AA), glycidyl methacrylate (GMA), acrylic acid-cage polysilsesquioxane (POSS) or a combination of the two or more thereof.

3. The in-situ polymerization preparation method of a polymer solid electrolyte having a fluorine-free interface layer according to claim 1, characterized in that: The organic solvent is: ethylene glycol dimethyl ether (DME), 1,2-dimethoxypropane (DMP), propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl formate (MF), methyl acetate (MA), N,N'-dimethylacetamide (DMA), fluoroethylene carbonate (FEC), methyl propionate (MP), ethyl propionate (EP), ethyl acetate (EA), γ-butyrolactone (GBL), tetrahydrofuran (THF), 2 -methyltetrahydrofuran (2MeTIF), 4-methyl-1,3-dioxolane (4MeDOL), dimethoxymethane (DMM), triethylene glycol dimethyl ether (DG), dimethyl sulfone (MSW), vinyl sulfite (ES), propylene sulfite (PS), dimethyl sulfite (DMS), diethyl sulfite (DES), 1,3-dioxolane (DOL), tetrahydrofuran (THF), vinylene carbonate (VC), fluoroethylene carbonate (FEC), and trioxymethylene (TOM) One or more combinations thereof.

4. The in-situ polymerization preparation method of a polymer solid electrolyte having a fluorine-free interface layer according to claim 1, characterized in that: The metal lithium salt is: lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonate)imide [LiN(CF3SO2)2, LiTFSI] and its derivatives, perfluoroalkyl lithium phosphate [LiPF3(C2F5)3, LiFAP], lithium tetrafluorooxalate phosphate [LiPF4(C2O4)], lithium bis(oxalate oxalate borate) (LiDFOB), lithium bis(oxalate borate) (LiBOB), lithium tri(catechol) phosphate (LTBP), sulfonated polysulfonamide lithium salt, lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium nitrate (LiNO3), lithium carbonate (LiCO3), lithium chloride (LiCl) or a combination of more thereof.

5. The in-situ polymerization preparation method of a polymer solid electrolyte having a fluorine-free interface layer according to claim 1, characterized in that: The initiator is: azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), azobisisovaleronitrile (AMBN), azoisobutylcyanamide (CABN), azobiscyclohexylcarbonitrile (ACCN), dimethyl azobisisobutyrate (AIBME), azobisisobutylamidine hydrochloride (AIBA), benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, diisopropylbenzene peroxide, benzene peroxide Tert-butyl formate, tert-butyl peroxyvalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, potassium persulfate, sodium persulfate, ammonium persulfate, 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone or a combination of more thereof.

6. The in-situ polymerization preparation method of a polymer solid electrolyte having a fluorine-free interface layer according to claim 1, characterized in that: The mass percentage of the initiator to the monomer is 0.01%-10%.

7. A polymer solid electrolyte without a fluorine interface layer, characterized in that: The polymer solid electrolyte of the fluorine-free interface layer is prepared by the in-situ polymerization preparation method of the polymer solid electrolyte of the fluorine-free interface layer according to any one of claims 1 to 6.

8. Use of the polymer solid electrolyte without fluorine interface layer according to claim 7 in the preparation of lithium metal batteries.

Citation Information

Patent Citations

  • In-situ prepared cyclocarbonate-based polymer electrolyte and application thereof in solid-state lithium battery

    CN110218276A

  • Non-combustible gel polymer electrolyte as well as preparation method and application thereof

    CN111253523A

  • Application of polymerization monomer, in-situ polymerization electrolyte and method for preparing all-solid-state secondary battery by using in-situ polymerization electrolyte

    CN115594803A

  • Gel polymer, battery and preparation method thereof

    CN117986460A

  • High-ionic-conductivity in-situ copolymerization gel electrolyte and preparation method and application thereof

    CN118899526A